Economic and Environmental Effects of Airline Deregulation - Youdi Schipper; Piet Rietveld (Tinbergen Institute, 1997)
This paper deals with the issue of regulatory reform in the airline industry, in connection with environmental externalities. Deregulation has led to shorter routes, higher frequencies, probably larger aircraft sizes and more intense peak traffic at airports. In addition, deregulation has led to lower average real fares, although various barriers to entry still allow carriers to keep prices above competitive levels. Environmental effects have thus far not received much attention in the discussion on deregulation. The paper contains a discussion of various types of environmental effects of aviation. An analytical model is developed to compare these effects in hub and spoke systems with a fully connected system. The conclusion is that for CO2 emissions private cost considerations and environmental considerations may run parallel in the choice of transport network, but that for other types of pollutants there may be a clear conflict. In addition the paper pays attention to equity aspects of externalities.
Keywords: 330; Luftverkehrspolitik; Umweltschutz; Theorie